Erosion and sediment transport modelling to inform payment for ecosystem services schemes - Benisiewicz, Barbara; Momblanch, Andrea; Leggatt, Alister; Holman, Ian P. (Springer, 2020)
Erosion and the impacts of the redistribution of sediment are a serious threat to the quality of water resources. They cause losses and/or additional expenses in many areas, such as water treatment, biodiversity or fisheries. The implementation of catchment management measures, aimed at preventing the transfer of sediment to rivers, can be a cost-beneficial way to address the problem. In order to select the measures and appropriate locations for erosion control, the spatially distributed soil erosion and sediment delivery model WaTEM-SEDEM was used. The model was calibrated against total suspended solids data at the outlet of the Wey catchment, South-east England, yielding satisfactory results. Different scenarios of catchment management were modelled to reduce the amount of sediment transported to the river. Scenarios introducing 24 retention ponds, 50-m-wide buffer strips and cover crops in areas with the largest erosion and sediment delivery were tested. The largest decrease in both sediment production and sediment export was obtained using cover crops, with reductions of 13.4% and 14.1%, respectively. A cost-benefit analysis considering multiple ecosystem services (e.g. control of erosion rates, attenuation of mass flow, pest control, wildlife and its outputs) identified the cover crops as the most cost-beneficial measure and a possible funding scheme based on payments for ecosystem services was developed as a way to enable its implementation.
Keywords: Soil loss; Sediment export; WaTEM-SEDEM; Retention ponds; Buffer strips; Cover crops; Catchment management